State-permeated capitalism in large emerging economies - Nölke, Andreas 1963-; Ten Brink, Tobias; May, Christian; Claar, Simone (Routledge, 2020)
"This book systematically analyzes the economic dynamics of large emerging economies from an extended Comparative Capitalisms perspective. Coining the phrase 'state-permeated capitalism', the authors shift the focus of research from economic policy alone, towards the real world of corporate and state behaviour"--
Keywords: Government corporations / Developing countries; Government business enterprises / Developing countries; Industrial policy / Developing countries